2007
DOI: 10.1038/nn1998
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism suppressing glycogen synthesis in neurons and its demise in progressive myoclonus epilepsy

Abstract: Glycogen synthesis is normally absent in neurons. However, inclusion bodies resembling abnormal glycogen accumulate in several neurological diseases, particularly in progressive myoclonus epilepsy or Lafora disease. We show here that mouse neurons have the enzymatic machinery for synthesizing glycogen, but that it is suppressed by retention of muscle glycogen synthase (MGS) in the phosphorylated, inactive state. This suppression was further ensured by a complex of laforin and malin, which are the two proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
358
0
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 329 publications
(388 citation statements)
references
References 42 publications
18
358
0
7
Order By: Relevance
“…20 In addition, we previously showed that neuron-specific hyperactivation of GS and the subsequent accumulation of glycogen severely compromise neuronal function and survival. 17,21 All together, these data raise the question as to why neurons express MGS if they do not accumulate the polysaccharide under normal conditions and would be unable to degrade it.…”
Section: Introductionmentioning
confidence: 99%
“…20 In addition, we previously showed that neuron-specific hyperactivation of GS and the subsequent accumulation of glycogen severely compromise neuronal function and survival. 17,21 All together, these data raise the question as to why neurons express MGS if they do not accumulate the polysaccharide under normal conditions and would be unable to degrade it.…”
Section: Introductionmentioning
confidence: 99%
“…Several potential targets for malin have been proposed, including laforin (22), glycogen synthase (GS) (23), the glycogen debranching enzyme, amylo-1,6-glucosidase,4-␣-glucanotransferase (AGL) (24), and the type 1 phosphatase regulatory subunit protein targeting to glycogen (PTG) (23,25) (see "Discussion"). Candidate substrates for laforin have been more elusive.…”
mentioning
confidence: 99%
“…Despite expressing all the necessary enzymes for glycogen synthesis, this pathway remains mostly inactive in neurons [27]. At the cellular level, glycogen biogenesis from glucose requires the sequential activities of hexokinase (glucose / glucose-6-phosphate), phosphoglucomutase (glucose-6-phosphate / glucose-1-phosphate), uridine diphosphate (UDP)-glucose pyrophosphorylase (glucose-1-phosphate / UDP-glucose) and glycogen synthase, which adds glucosyl residues from UDP-glucose to the glycogen molecule via a-(1,4) bonds.…”
Section: Brain Glycogenmentioning
confidence: 99%